Sosialisasi Ketentuan Hukum Merek Well Known Mark Dalam Pembelian Barang Melalui Online Bagi Siswa SMA Negeri 3 Medan - Sari, Bina Era Dany (Jurnal Pengabdian Masyarakat Inovasi, 2024)
The rapid development of information technology has transformed societal consumption patterns, particularly among adolescents who are highly active in online shopping transactions. However, this convenience is often accompanied by the widespread distribution of counterfeit goods of well-known marks, which infringe upon the exclusive rights of brand owners and mislead consumers. This community service activity aims to enhance the legal literacy of students at SMA Negeri 3 Medan regarding the protection of well-known marks in electronic transactions. The implementation method utilized legal education through interactive lectures, group discussions, and legal case studies conducted directly at SMA Negeri 3 Medan, involving 40 students as participants. Data analysis was performed using a descriptive qualitative approach to capture changes in students' understanding before and after the activity. The results of the service show that prior to the socialization, the majority of students did not understand the legal aspects of trademarks and considered purchasing counterfeit or "KW" goods as a common practice. Following the intervention, there was a significant increase in legal awareness, where students were able to identify the criteria for well-known marks based on Law Number 20 of 2016 and the principle of good faith in the ITE Law. The conclusion of this activity emphasizes that continuous legal education for the younger generation is highly effective in preventing intellectual property rights violations in the digital market. Collaboration between academics and educational institutions is essential to establish a strong legal culture in transactions during the era of economic globalization.